1986
DOI: 10.1007/bf00687045
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of S-100 protein in neurofibroma

Abstract: The nature of the cells in neurofibromas was studied by electron microscopy and immunoelectron-microscopic examination of S-100 protein. Ultrastructurally, all five neurofibromas studied were found to be composed of Schwann cells, perineurial cells, and intermediate cells, which had features of both perineurial cells and fibroblasts. The Schwann cells had complex, branched cytoplasmic processes and a continuous basal lamina. The perineurial cells were distinguishable from Schwann cells by the presence of numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 20 publications
3
42
3
Order By: Relevance
“…Our immunohistochemical results may also suggest the presence of intermediate The constituents of neurofibromas are still controversial (9). Ultrastructural studies suggested the presence of perineurial cells, endoneurial fibroblasts, and intermediate cells, as well as Schwann cells (5,8). However, the heterogeneous cell populations have not been confirmed immunohistochemically (9,16,17).…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Our immunohistochemical results may also suggest the presence of intermediate The constituents of neurofibromas are still controversial (9). Ultrastructural studies suggested the presence of perineurial cells, endoneurial fibroblasts, and intermediate cells, as well as Schwann cells (5,8). However, the heterogeneous cell populations have not been confirmed immunohistochemically (9,16,17).…”
Section: Discussioncontrasting
confidence: 41%
“…Furthermore, there were a few cells exhibiting both perineurial (Glut1) and fibroblastic (CD34) immunophenotypes at the peripheral areas close to the capsule. Some ultrastructural studies of neurofibromas indicated the presence of an intermediate type of cells, between perineurial cells and fibroblasts (5,8). Our immunohistochemical results may also suggest the presence of intermediate The constituents of neurofibromas are still controversial (9).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Neuro fibromas consist of Schwann cells with S100 protein and also contain cells without S100 protein, namely perineu rial, intermediate cells and endoneurial fibroblasts. 16 CD 34 positive stromal cells are typically seen in neuro fibromas. 17,18 Calretinin was cited as an aid to distin guish schwannomas from neurofibromas by Fine et al 19 Calretinin is strongly expressed by schwannomas.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence is associated with increased morbidity and fatality, with progression to malignancy occurring in about 6% of NF1 patients. Although neurofibromas show marked cellular heterogeneity, Schwann cells (SCs) are the major cell type amplified and typically comprise 40-80% of the tumor cells (Hirose et al, 1986;Krone et al, 1986). Moreover, cumulative evidence indicates that neurofibromas contain a clonal population of Schwann cells that have disruptive mutations on the remaining NF1 allele .…”
Section: Plexiform-like Neurofibromas Develop Inmentioning
confidence: 99%